2014
DOI: 10.1002/chem.201402655
|View full text |Cite
|
Sign up to set email alerts
|

Chloride‐Induced Aufbau of Perchlorinated Cyclohexasilanes from Si2Cl6: A Mechanistic Scenario

Abstract: A surprisingly simple preparative procedure, addition of Si2Cl6 to a solution of [nBu4N]Cl in CH2Cl2, leads to the formation of the chloride-complexed cyclic dianions [Si6Cl12⋅2Cl](2-), [(SiCl3)Si6Cl11⋅2Cl](2-), or [1,y-(SiCl3)2Si6Cl10⋅2Cl](2-) (y = 1, 3, 4), depending on the stoichiometric ratio of the reactants and the reaction temperature (25-85 °C). Below -40 °C the open-chain oligosilane chloride adducts [Si3Cl9](-), [Si3Cl10](2-), [Si4Cl11](-), and [Si6Cl15](-) are formed, again depending on the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
109
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(118 citation statements)
references
References 20 publications
4
109
0
5
Order By: Relevance
“…While the two Ge-Cl bond lengths are almost the same (Ge1-Cl1: 2.2094(14) Å, Ge2-Cl4: 2.2011(15) Å) within a range of standard deviations, the orientation of the two Cl atoms are slightly different to each other. That is, one of the Cl atom (Cl4) is oriented to outside of the five-membered ring skeleton, but another one (Cl1) is approaching to the central Si atom with the Cl1···Si distance of 3.25 Å, which is far from the other one (Cl4···Si = 3.66 Å) [27]. In addition, the two Cl-Ge-Si angles are considerably different from each other, (Cl1-Ge1-Si = 90.20 (8), Cl4-Ge2-Si = 105.40 (8)).…”
Section: Resultsmentioning
confidence: 99%
“…While the two Ge-Cl bond lengths are almost the same (Ge1-Cl1: 2.2094(14) Å, Ge2-Cl4: 2.2011(15) Å) within a range of standard deviations, the orientation of the two Cl atoms are slightly different to each other. That is, one of the Cl atom (Cl4) is oriented to outside of the five-membered ring skeleton, but another one (Cl1) is approaching to the central Si atom with the Cl1···Si distance of 3.25 Å, which is far from the other one (Cl4···Si = 3.66 Å) [27]. In addition, the two Cl-Ge-Si angles are considerably different from each other, (Cl1-Ge1-Si = 90.20 (8), Cl4-Ge2-Si = 105.40 (8)).…”
Section: Resultsmentioning
confidence: 99%
“…Several years later,i tw as reported that 1 should disproportionate into SiCl 4 and Si 5 Cl 12 under the catalytici nfluence of trimethylamine. [2] For the next 40 years,the mechanism remained ambiguous because no concrete evidencea boutt he intermediates was obtained.…”
Section: Introductionmentioning
confidence: 98%
“…[2] For the next 40 years,the mechanism remained ambiguous because no concrete evidencea boutt he intermediates was obtained. Recently,s ingle crystals of Si 5 Cl 12 and amine-complexed dichlorosilylene (SiCl 2 ·NR 3 )w ere obtained as key intermediates through low-temperaturet wo-dimensional HETCOR NMR spectroscopy measurements and calculations. [3] In 2012, the reactiono fa nother tertiarya mine, tetramethylethylenediamine (TMEDA), with 1 was reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key to these developments have been the usage of suitable synthetic methodologies in combination with thermodynamic and kinetic stabilization by appropriately chosen ligands. In particular, for the heavier carbon analogue silicon, a plethora of studies reported new low-valent compounds in recent years [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and the chemistry of silylene base adducts has already been carefully developed [14,[26][27][28][29][30][31][32][33][34][35][36]. Before these findings, silyliumylidene ions, cationic Si(II) species were found to be promising as similar versatile Lewis amphiphiles [37,38].…”
Section: Introductionmentioning
confidence: 99%